Issues surrounding end-of-life decision-making - Tejwani, Vickram (Dove Medical Press, 2013)
End-of-life decision-making is a complex process that can be extremely challenging. We describe a 42-year-old woman in an irreversible coma without an advance directive. The case serves to illustrate the complications that can occur in end-of-life decision-making and challenges in resolving difficult futility disputes. We review the role of advance directives in planning end-of-life care, the responsibility and historical performance of patient surrogates, the genesis of futility disputes, and approaches to resolving disputes.